Energy efficiency overestimated by classic affinity laws: relation between volumetric flow rate and static pressure of an axial mine fan adjusted by a variable frequency driver. Issue 3 (3rd July 2019) - Tian, Feng; Wang, Hai-qiao; Chen, Shi-qiang; Zhu, Zhu-long
ABSTRACT: A significant problem with operating a coal mine fan is finding ways to save energy while still maintaining the required air supply to working faces. The authors developed and tested the performance of a K45-4-№9/18.5 kW axial mine fan adjusted by a variable frequency driver set to different fractions of a typical national electric grid frequency of 50 Hz. Its volumetric flow-rate and static pressure (Q-H) data were fitted with fifth-order polynomial equations using least-squares regression. The extremes of the Q-H curves descend with decreasing frequency and differ significantly from the predictions of classic affinity laws (CAL) in fluid dynamics. The air-flow power predicted by CAL theory deviates from the baseline of the fifth-order polynomial extremes by a maximum of 48%. Interestingly, the deviation between theoretical and experimental values increases with decreasing power frequency. These results are evidence of the theoretical overestimation of energy efficiency of an AMF adjusted by a VFD.